Notice of the Sword-Belt of the Sword of State of Scotland, restored in 1892 to the Scottish Regalia by the Rev. Samuel Ogilvy Baker - Brook, Alexander J S (Proceedings of the Society of Antiquaries of Scotland, 1894)